Q: How do you factor x2 plus 17x plus 52?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x+13)(x+4)

Assuming this expression equals zero, it factorises as (x + 4)(x + 13) making x either -4 or -13.

x3 + x2 - 17x + 15 = (x - 1)(x - 3)(x + 5). Thus, the zeros are 1, 3, and -5. All three zeros are rational.

It is x+9, provided that x is not -8.

Y = X2 + 18X + 52 set to 0 X2 + 18X + 52 = 0 subtract 52 from each side X2 + 18X = - 52 now, halve the coefficient of the variable term (18), square it and add it to both sides X2 + 18X + 81 = - 52 + 81 now, factor on left and gather terms on right (X + 9)2 = 29 (X + 9)2 - 29 = 0 ---------------------------vertex form

Related questions

(x+13)(x+4)

(x + 1)(x + 3)(x - 5)

(x + 3)(4x + 5)

Assuming this expression equals zero, it factorises as (x + 4)(x + 13) making x either -4 or -13.

4(x2 - 6x + 13)

x3 + x2 - 17x + 15 = (x - 1)(x - 3)(x + 5). Thus, the zeros are 1, 3, and -5. All three zeros are rational.

It is x+9, provided that x is not -8.

Y = X2 + 18X + 52 set to 0 X2 + 18X + 52 = 0 subtract 52 from each side X2 + 18X = - 52 now, halve the coefficient of the variable term (18), square it and add it to both sides X2 + 18X + 81 = - 52 + 81 now, factor on left and gather terms on right (X + 9)2 = 29 (X + 9)2 - 29 = 0 ---------------------------vertex form

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)

x + 4

x2(x3 + 1) is the best you can do there.

(x + 8)(x + 9)